PERANAN PENDIDIKAN AGAMA HINDU MENGHADAPI DEGRADASI MORAL PESERTA DIDIK PADA PRA DAN MASA PANDEMI COVID-19 - Ni Made Muliani (Guna Widya: Jurnal Pendidikan Hindu, 2022)
The study aims to analyze the implication of learning Hindu religious education in dealing with the moral degradation of learners. The method used in this research is qualitative through literature studies. The results and conclusions of this study are 1) The factors that cause Hindu religious education to be able to deal with the moral degradation of learners in the pre and covid-19 pandemic period, namely the purpose and function of Hindu religious education in line with the national education objectives of the Republic of Indonesia; 2) The process of Hindu religious education in the face of moral degradation of learners in the pre and covid-19 pandemic period, namely: (a) kindergarten level must be done through habituation and fun learning activities both online and offline; (b) the level of primary education; (c) secondary education; (d) higher education and (e) 4 pillars of education according to UNESCO; 3) Implications of Hindu religious education in the face of moral degradation of learners in the pre and covid-19 pandemic, namely: (a) Realizing the national educational objectives of the Republic of Indonesia; (b) help create mental resilience in carrying out positive things and stay away from the negatives of modernization, globalization and foreign cultures; (c) help preserve the Hindu religious values and culture of the Indonesian nation and help realize Indonesia's progress by 2045